Insights into Organic Carbon, Iron, Metals and Phosphorus Dynamics in Freshwaters - Shirokova, Liudmila S. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Organic carbon (OC), nutrients and trace metals are key aquatic components of freshwater systems, including groundwater, soil water, lakes, rivers, and their estuaries. Over the past decade, there has been increasing interest regarding the rising in organic carbon and iron concentrations in freshwaters in relation to the so-called "browning" effect, caused by climate warming and changes in anthropogenic pressure. As for phosphorus, it is a vital element for all aquatic ecosystems and its aquatic biogeochemical cycle now undergoes sizable changes linked to eutrophication, invasive species development, and transformations between organic and inorganic forms. This book combines the articles dedicated to various aspects of the behavior of organic carbon, phosphorus, iron (and other related metals) in a broad range of freshwater environments, from soil solutions and groundwaters to ponds, lakes, rivers, and their riparian zones and estuaries.